Pendampingan dan Pengembangan Profesionalisme Guru di Era Digital: Program Berbasis Kajian Pustaka Sistematis - Sianturi, Tama Roma P.; Purba, Herlina Mariana; Fitrianti, Fitrianti; Azainil, Azainil (Sekolah Tinggi Teknologi Industri (STTI) Bontang, 2024)
In the current educational landscape, the integration of digital technology has become essential, shifting traditional teaching methods and demanding teachers to acquire new skills. This community service program aims to assist and develop teacher professionalism in the digital era. We identify the challenges faced by educators, explore opportunities for utilizing digital tools, and propose effective strategies for integrating technology into education. Through a systematic literature review and insights from various scholarly sources, this program focuses on themes such as the integration of technology in teacher training, promoting digital citizenship, and ensuring high-quality digital professional development. The program highlights the complexity of teacher professionalism in the digital age and emphasizes the importance of continuous professional development to equip educators to keep pace with technological advancements. Additionally, this program underscores the transformative potential of digital tools such as AI, AR, VR, and digital data analysis in enhancing teaching outcomes. The implications indicate the need for collaboration among policymakers, educational leaders, and practitioners to invest in innovative strategies, ensure equitable access to technology, foster collaborative learning communities, and offer ongoing support for educators. By embracing digitalization and prioritizing professional growth, teachers can enhance student learning and prepare them for a more technologically advanced future.